Involvement of HSP90 in ischemic postconditioning-induced cardioprotection by inhibition of the complement system, JNK and inflammation - Wang,Dong-Xiao (2020)
Abstract Purpose To investigate whether heat shock protein 90 (HSP90) is involved in complement regulation in ischemic postconditioning (IPC). Methods The left coronary artery of rats underwent 30 min of occlusion, followed by 120 min of reperfusion and treatment with IPC via 3 cycles of 30s reperfusion and 30s occlusion. The rats were injected intraperitoneally with 1 mg/kg HSP90 inhibitor geldanamycin (GA) after anesthesia. Eighty rats were randomly divided into four groups: sham, ischemia-reperfusion (I/R), IPC and IPC + GA. Myocardial infarct size, apoptosis index and the expression of HSP90, C3, C5a, tumor necrosis factor (TNF)-alpha, interleukin (IL)-1β and c-Jun N-terminal kinase (JNK) were assessed. Results Compared with the I/R injury, the IPC treatment significantly reduced infarct size, release of troponin T, creatine kinase-MB, and lactate dehydrogenase, and cardiomyocyte apoptosis. These beneficial effects were accompanied by a decrease in TNF-α, IL-1β, C3, C5a and JNK expression levels. However, all these effects were abrogated by administration of the HSP90 inhibitor GA. Conclusion HSP90 exerts a profound effect on IPC cardioprotection, and may be linked to the inhibition of the complement system and JNK, ultimately attenuating I/R-induced myocardial injury and apoptosis.